An assessment of stress coping for mental health promotion among Information Technology employees in Japan - Makie Nagai; Yuko Morikawa; Yuko Hamazaki; Hideaki Nakagawa (Archives of Depression and Anxiety - Peertechz Publications, 2019)
Primary health care for mental health in workers should apply to actualities of workers' stress coping and stress response. We conducted an assessment by cross-sectional study concerning stress coping, job stress, and stress response among IT employees in Japan.  Subjects were 75 healthy new employees (males). We used the 54-item Maslach Burnout Inventory-General Survey (MBI-GS, domains: exhaustion, cynicism, professional efficacy), the Job Content Questionnaire (JCQ, domains: demand, control, social support), the General Coping Questionnaire (GCQ, domains: emotion expression, emotional support seeking, cognitive reinterpretation, problem solving).    All subjects attained high scores for job demand. High scores for the coping domains emotional expression was associated with high scores for the burnout domain cynicism (p=0.019). High scores for the coping domains cognitive reinterpretation associated with low scores for the burnout domain cynicism (p=0.002).  The result suggested that high expressing emotion which is not usual their coping associated to low concern and passion for work. Furthermore, cognitive reinterpretation against stress factors associated to passion for work.